Correction of Rippling in Implant-based Breast Reconstruction with Serratus Fascia Flap. Issue 3 (10th March 2023) - Faenza, Mario; Lanzano, Giuseppe; Grella, Elisa; Izzo, Sara; Ferraro, Giuseppe Andrea
Abstract : Summary: Implant-based breast reconstruction represents the most popular procedure for the treatment of women undergoing skin-sparing mastectomy. In selected patients, it allows for obtaining an excellent appearance of the reconstructed breast with great satisfaction to the patient. However, aesthetic and functional results can be affected by complications requiring reoperation. Among them, rippling is an undesired occurrence associated with implant-based reconstruction. It consists of a cutaneous manifestation, visible and/or palpable, of the implant wrinkles and edge which appear mostly when the patient leans forward. To treat this contour deformity, several techniques have been described such as acellular dermal matrices and autologous tissues. In this study, we intend to add the serratus anterior fascial flap within the autologous options in the treatment of implant rippling, reporting our experience.